Optimization of Organic Fertilizer Rice Washing Water and Planting Patterns on the Growth and Production of Cayenne Pepper (Capsicum frutescens L.) Plants: Optimalisasi Pupuk Organik Air Cucian Beras Dan Pola Tanam Terhadap Pertumbuhan Dan Produksi Tanaman Cabai Rawit (Capsicum frutescens L.) - Hamidah Hamidah; Ahmad Andi (Universitas Widya Gama Mahakam, 2020)
The increasing market demand causes organic farming to grow rapidly along with the optimization of health understanding. Organic agricultural products are popular with middle and upper class people who are willing to pay higher prices for healthy, safe and environmentally friendly food products. The purpose of this study was to determine the optimal use of organic rice washing water and cropping patterns in the field for the growth and yield of F1 chili varieties. The research was carried out in Kelurahan Gunung Kelua, Samarinda, East Kalimantan for approximately 4 (four) months, namely from October to February 2020. This study used a Randomized Group Design which was arranged in factorial 3x2 with 2 replications. The first factor is liquid organic fertilizer consisting of 3 (three) levels including: P0 without treatment, P1 (liquid organic fertilizer 250 ml l-1 water), P2 (liquid organic fertilizer 500 ml l-1 water). The second factor is the cropping pattern which consists of 2 (two), namely T1 with Monoculture planting pattern, T2 with intercropping cropping pattern. The results showed that the use of liquid organic fertilizer rice washing water can increase the growth and production of chilli F1 variety and intercropping cropping patterns as optimal land use in the field.